Black woods, blue sky : a novel - Ivey, Eowyn (Random House, 2025)
"Birdie splits her days between caring for her six-year-old daughter, Emaleen, and working as a waitress at a roadside lodge in Alaska. But this is not the life she'd dreamed of as a child. Back then, she had fantasized about being free in the world of nature. Arthur is a soft-spoken recluse--adopted as a boy under mysterious circumstances by a local couple who raised him as their own but understood that he could never fully fit into their world. He calls the mountains on the far side of the Wolverine River his home and lives completely off the grid, appearing in the town at random intervals. But when he shows up at Birdie's lodge one day and she serves him honey and tea, the two form a friendship, and as they eventually fall in love Birdie begins to imagine a different life for herself and her daughter. When Birdie and Emaleen move to Arthur's remote cabin life initially seems idyllic; they spend their days catching fish, picking berries, and playing games in the sunshine. But as the days shorten Birdie begins to realize that the truth of Arthur's life is much more complicated and mysterious than she understood, and that the reality of who he is may be putting her and her daughter's life in danger."--